A generation lost?: Prolonged effects of labour market entry in times of high unemployment in the Netherlands. (December 2016) - Wolbers, Maarten H.J.
Highlights: The permanence of initial labour market disadvantages for Dutch cohortswas studied. Synthetic cohort analysis was applied on the basis of repeated cross-sections. Negative effects on chances of work and attained level of occupation were detected. These negative effects started to dissipate after a few years on the labour market. High initial unemployment does not produce a lost generation of young people. Abstract: After the economic crisis of the 1980s, concerns arose about whether the high youth unemployment at that time would produce a 'lost generation' of young people in the Netherlands. The same concerns have recently arisen about the potential effects of the current high rate of youth unemployment. The issue is just how justified such concerns are. In order to answer this question, we investigated the permanence of initial labour market disadvantages for cohorts of young people in the Netherlands. Repeated cross-sections of the Dutch Labour Force Survey (1993–2011) were used and a synthetic cohort analysis was applied in order to 'follow' cohorts of young people throughout their early years on the labour market. Negative effects of high initial unemployment on later chances of work and attained level of occupation were detected. However, these negative effects started to dissipate after a few years on the labour market. These findings show the average negative effects of high initial unemployment on labour market entry to not be permanent: young people in the Netherlands experience negative effects of initially high unemployment on labour market entry, but these effects do not produce a lost generation.